Elafin selectively regulates the sensitivity of ovarian cancer cells to genotoxic drug-induced apoptosis - Wei, Huafeng (2012)
OBJECTIVE: Elafin has been reported to be abundantly expressed in human epithelial ovarian carcinoma (EOC), however, its functions are poorly understood. Here, we evaluated the role of elafin in modulating the sensitivity of human EOC cells to chemotherapeutic drugs. METHODS: Elafin expression was determined by ELISA in 9 established human EOC cell lines. A lentivirus encoding elafin-specific shRNA was used to down-regulate elafin expression in OVCAR3 and OV433 cells, and a plasmid encoding elafin was used to ectopically express elafin in elafin-negative SKOV3 cells. Sensitivity to cisplatin and other genotoxic agents and to paclitaxel, an inhibitor of microtubule depolymerization, was examined in OVCAR3, OV433 and SKOV3 sublines. Cell viability was determined by the MTT assay, apoptosis by annexin V/7-AAD staining and caspase activation by fluorimetric assay. RESULTS: Knockdown of the elafin gene decreases cisplatin IC50 by at least 2-fold in OVCAR3 and OVCAR433 cells (p<0.01) but does not affect paclitaxel IC50. The sensitivity to other genotoxic agents such as carboplatin, cyclophosphamide and 5-fluorouracil was also increased by silencing the expression of elafin. Apoptosis and caspase-3 activation was significantly augmented in cisplatin-treated OVCAR3 cells with silenced elafin. Overexpression of elafin in SKOV3 cells made them more resistant to cisplatin and decreased cisplatin-induced apoptosis and caspases activation (p<0.01). CONCLUSIONS: Expression of elafin decreases the sensitivity of human EOC cells to several genotoxic agents, which may have an important implication in predicting the response of patients with EOC to chemotherapy in the clinic.